Impact of different grades of anaemia severity during pregnancy on maternal and neonatal outcomes: a prospective study - Dahiya, Sonia; Malik, Nisha; Pandey, Kiran; Gupta, Renu; Perumal, Vanamail; Singh, Vikram (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Anaemia in pregnancy is a universal health problem that may cause a number of obstetrical and neonatal complications. This prospective observational study aims to evaluate and compare maternal and neonatal outcomes in different grades of anaemia severity. Methods: A total of 400 pregnant women with anaemia in third trimester were classified into three groups according to haemoglobin (Hb) levels-group I with Hb:10-10.9 g/dl, group II with Hb:7-9.9g/dl and group III with Hb<7 g/dl. Maternal and neonatal outcomes of women with different severity of anaemia were analyzed and compared. Two groups means were compared by Student’s t-independent test and more than two groups means by one way analysis of variance test followed by post-hoc pairwise comparison using Bonferroni test. Results: The prevalence of anaemia in the study population was 35.2%. Mild, moderate and severe anaemia were found in 58% (n=232), 29.0% (n=116) and 13% (n=52) women respectively. A statistically significant difference in maternal outcomes such as Preterm labor (p=0.001), Prelabor premature rupture of membranes (p=0.044), Intrauterine growth restriction (p=0.002) and postpartum hemorrhage (p=0.001) was observed amongst the three groups. Cardiac failure occurred in 26.9% (n=14) and mortality in 13.4% (n=7) women with severe anaemia. Amongst the neonatal morbidities, the rate of low birth weight, preterm birth, respiratory distress syndrome, septicaemia, pneumonitis and jaundice revealed an increasing trend with rising severity of anaemia which was statistically significant. Conclusions: Targeted interventions addressing early detection and appropriate treatment in early pregnancy can prevent and avoid dismal maternal and neonatal consequences.